A fundamental equation - Mačys, Juozas Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2017)
Very important and instructive trigonometric equation is considered. The solutionsfrom different manuals and reference books are examined, mistakes of these solutionsare discovered. It is shown how to make the solution of the equation shorter, how to presentthe answer more visually.
Keywords: trigonometric equations; inverse trigonometric functions; different methods of solution; answer forms